Interactive song composer / Nur Suria Mansor - Nur Suria, Mansor (2006)
The important of sounds as a channel of communication is emphasized and attention is drawn to some of its special properties. The success of the music industry and the importance of sound and music to film indicate how a substantial element of our culture relies on our sensitivity to sound, both to provide information and emotional effect. Usually people develop musical skills through formal stud y and practical application. Much of the musical skills are absorbed unconsciously as part of the music-making experience. With the existent of recent multimedia technology. there are alternative ways to learn music in fun and interactive environment. "Interactive Song Composer" is one of an interactive multimedia system that allows user to learn more about composing sound. It is stand alone system that allows user to select and combines the provided Midi's according to their creativity to produce a new kind of sound / MIDI.